Impact of Internal Factors on the Debt Decisions: A Study of Listed Capital Goods Companies in the Colombo Stock Exchange, Sri Lanka - Mithila, G.; Lingesiya, K. (International Conference on Business Management (ICBM 2025), 2025)
This study investigates the determinants of internal company factors influencing debt financing decisions among listed capital goods companies, a sector that accounts for one of the largest daily turnover sectors among the non-financial companies listed in Sri Lanka. Using panel data from 25 companies within the sector for 10 years (from April 2015 to March 2024), the analysis applies pooled, fixed and random effect tests to explore the relationship between internal factors and debt financing. The study considers Profit Margin (PM), Liquidity level (LIQ), Tangible Fixed Asset (FA), Tax Shield from Non-Interest expenses (TSNI), Cash generated from Operating activities (CO), Cash generated from Investment activities (CI), Average Interest rate paid by the company (INT) as key determinants of internal financing decisions while to measure the debt financing of the companies, total Debt to Total Assets (DA) and Debt to Equity (DE) ratios are utilised. The findings reveal that PM and LIQ, CO and INT negatively and significantly impact DA and DE, suggesting firms with higher profitability, liquidity, internal cash generation or higher financing costs are less reliant on debt financing. On the other hand, TFA and TSNI positively influence DA, highlighting the role of collateral and tax benefits in leveraging decisions. FS and CI are found to be insignificant. Hence this study highlights the importance of considering Profitability, Liquidity, Cash from operations, Non- Debt Tax Shield, Interest rate and Asset Tangibility in making debt financing decisions. These results provide valuable insights for financial managers for optimising capital structure, future researchers in understanding sector-specific dynamics, and policymakers in developing frameworks to enhance corporate financial decision-making. By focusing on the capital goods sector, this research contributes to a broader understanding of financing behaviour within one of Sri Lanka’s key non-financial sectors.
Keywords: Capital Goods Companies; Determinants; Debt Decision; Internal Factors